Iminosugars With Endoplasmic Reticulum α-Glucosidase Inhibitor Activity Inhibit ZIKV Replication and Reverse Cytopathogenicity in vitro - Bhushan, Gitanjali; Lim, Levina; Bird, Ian; Chothe, Shubhada K.; Nissly, Ruth H.; Kuchipudi, Suresh V. (Frontiers in Microbiology, 2020)
Zika virus (ZIKV), a vector-borne virus of the family Flaviviridae, continues to spread and remains a significant global public health threat. Currently, there are no approved vaccines or antivirals against ZIKV. We investigated the anti-ZIKV ability of three iminosugars with endoplasmic reticulum α-glucosidase inhibitor (ER-AGI) activity, namely deoxynojirimycin (DNJ), castanospermine, and celgosivir. None of the three iminosugars showed any significant cytotoxicity in Vero or human microglia CHME3 cells when applied for 72 h at concentrations up to 100 μM. Iminosugar treatment of Vero or CHME3 cells prior to ZIKV infection resulted in significant inhibition of ZIKV replication over 48 h. Reduction in ZIKV replication in iminosugar-treated cells was not associated with any significant change in the expression levels of key antiviral genes. Following infection with three different strains of ZIKV, iminosugar-treated Vero or CHME3 cells showed no cell death, whereas vehicle-treated control cells exhibited 50–60% cell death at 72 h post-infection (hpi). While there was no significant difference in apoptosis between iminosugar-treated and control cells, iminosugar-treated cells exhibited a substantial reduction of necrosis at 72 hpi following ZIKV infection. In summary, iminosugars with ER-AGI activity inhibit ZIKV replication and significantly reduce necrosis without altering the antiviral gene expression and apoptosis of infected human cells. The results of this study strongly suggest that iminosugars are promising anti-ZIKV antiviral agents and such warrant further in vivo studies.